3x+5=-2(x-5)

Simple and best practice solution for 3x+5=-2(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+5=-2(x-5) equation:


Simplifying
3x + 5 = -2(x + -5)

Reorder the terms:
5 + 3x = -2(x + -5)

Reorder the terms:
5 + 3x = -2(-5 + x)
5 + 3x = (-5 * -2 + x * -2)
5 + 3x = (10 + -2x)

Solving
5 + 3x = 10 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
5 + 3x + 2x = 10 + -2x + 2x

Combine like terms: 3x + 2x = 5x
5 + 5x = 10 + -2x + 2x

Combine like terms: -2x + 2x = 0
5 + 5x = 10 + 0
5 + 5x = 10

Add '-5' to each side of the equation.
5 + -5 + 5x = 10 + -5

Combine like terms: 5 + -5 = 0
0 + 5x = 10 + -5
5x = 10 + -5

Combine like terms: 10 + -5 = 5
5x = 5

Divide each side by '5'.
x = 1

Simplifying
x = 1

See similar equations:

| 8r^2+23r=36 | | 9=-2-y | | 34x-13=55 | | 16a+2b=4 | | -15=5m^2+28m | | Y=8x^2+2x-3 | | -1x+3=-8 | | n+n+1+n+2=54 | | -6-2x=10-8 | | .25x+8=.62x+2 | | 15/(8n-32) | | 11x-33=8x+0 | | 2x^2-7x-70=3x | | 5p+2=4p-9 | | (-18)+q=5 | | 2t^2+5=2t^2+1 | | n+n+1+n+1=54 | | 15/8n-32 | | -5.9=k/3 | | 25m^2+2=3 | | 7-3x=5x+14 | | 10x-50=25 | | 3x-6x^2/x^3 | | x*0.65=28748 | | 100-38= | | 2x^2+31-9=0 | | a+2a+3a-b=7a-6 | | 5x-1=15x-72 | | 9(x+12)=18 | | 9=8+z | | 6k+2.3=-9.7 | | 2(2x-4)=3(x+3) |

Equations solver categories